(untitled) (Medical Forum Monthly, 2022)
Objective: To compare outcomes of single port sub-xiphoid VATS thymectomy with trans-sternal thymectomy. Study Design: Retrospective study Place and Duration of Study: This study was conducted at the Lady Reading Hospital Peshawar for 6 months, Medical records of last 5 years from January, 2018 to June, 2022. Materials and Methods: All patients that underwent thymectomy by sub-xiphoid VATS or trans-sternal approach were included. VATS indication included Masaoka stage I-II thymoma (diameter <5 cm). Patients were divided into two groups depending upon approach taken for thymectomy, viz. single port sub-xiphoid VATS and trans-sternal thymectomy. SPSS v23.0 was used for data analysis. To test for comparison between outcomes of sub-xiphoid and trans-sternal thymectomy, either independent t-test or Mann-Whitney U tests were applied keeping p-value <0.05 as statistically significant. Results: 70 patients underwent S-VATS while 55 T-VATS. Mean operative time, blood loss, post-operative pain, duration of chest tube and hospital stay in S-VATS group 87.68 ± 43.15 minutes, 78.19 ± 49.44 ml, 2.65 ± 0.59, 2.98 ± 1.29 days and 4.1± 1.88 days respectively. In T-VATS group, the mean values were 108.33 ± 45.25 minutes, 125.44 ± 98.15 ml, 5.2 ±1.21, 3.19 ± 2.11 days and 5.4 ± 2.14 days, respectively. A significant difference of p<0.01 was reported in-between both the groups [Table II]. A total of 10 post-operative complications were observed in S-VATS group while 14 in T-VATS group. Conclusion: Both intra-operative and post-operative outcomes were in favorable towards S-VATS when compared with that of T-VATS. Further studies are required to validate the findings of this study.